Alterations in the financial markets of the Baltic countries and Russia in the period of economic downturn - Dubinskas, Petras; Stungurienė, Stanislava (Technological and Economic Development of Economy, 2010)
The present article analyses the alternations in the causality in the financial markets during the 2008–2009 financial crisis with a clear focus on the changes and developments in the financial markets of the Baltic States and Russia in the period starting from 2008. The authors have advanced a hypothesis that the research methods of trends of an abrupt plunge and subsequent stabilistation of equity prices that were clearly discernable during the 1987 crisis are also pointfull for the current financial crisis. The present research was conducted on the basis of the following assumptions: both crises affected financial markets of several nations; a characteristic feature for the inception of the crises is an abrupt fall in equity prices; indications of stabilisation in financial markets become observable before financial experts conclude the end of the financial crisis. To confirm the hypothesis on the similarities of the general trends during the two major international financial crisis, the authors employed empiric tests developed on the basis of Granger causality tests. Based on the precedent survey of the financial crisis of 1987 (Malliaris and Urrutia 1992), the authors of the present article chose to use the Granger causality testing methodology. To be able to apply the Granger causality test first it was necessary to verify the degree of cointegration of the indices of the main equity markets in each of the country (OMX Vilnius, OMX Riga, OMX Tallinn, RTS). For that purpose the authors used the Dickey‐Fuller and Johansen testing methodology. Both methodologies demonstrated a strong cointegration between the changes in the indices of all equity markets irrespective of the period analysed (i.e., pre‐crisis, during the crisis, post‐crisis). In all cases the T‐statistics exceeded the critical value. The strongest cointegration was observable in the crisis period, and the weakest – after the crisis. The results showed that in view of the financial crisis the Latvian market showed the greatest degree of slow‐down despite it being most active in the pre‐crisis times, likewise, Estonian market also showed a somewhat higher degree of passiveness. Thus, it was the Latvian and Estonian markets that the financial downturn had the most painful impacts upon. While the Lithuanian and the Russian markets were, on the contrary, much more active and therefore outlived the equity crash period with least painful after‐effects, thus producing confirmation that in the face of a crisis the interests and expectations of most investors are largely related to major markets normally viewed as more reliable and showing a higher degree of resilience. Article in English. Finansų rinkų pokyčiai Baltijos šalyse ir Rusijoje ekonominio nuosmukio laikotarpiu Santrauka. Straipsnyje analizuojami finansų rinkų priežastingumo pokyčiai 2008–2009 m. finansinės krizės laikotarpiu. Pagrindinis dėmesys sutelkiamas į Baltijos šalių– Lietuvos, Latvijos ir Estijos – bei Rusijos akcijų rinkų pokyčius nuo 2008 m. Autoriai iškelia hipotezę, kad finansų rinkose staigaus akcijų kainų kritimo ir jų stabilizavimosi tendencijos, kurios išryškejo nuo 1987 m. prasidėjusios krizės, būdingos dabartinei finansinei krizei. Tyrimo metu daromos prielaidos: abi krizės apima daugelio valstybių finansų rinkas; krizių pradžiai būdingas staigus akcijų kainų kritimas; finansų rinkų stabilizavimosi požymiai pastebimi anksčiau, nei ekspertai konstatuoja krizės pabaigą. Dviejų tarptautinių finansų rinkų krizių bendrųjų tendencijų panašumo hipotezei patvirtinti naudoti empiriniai testai, parengti remiantis Granger priežastiniais testais: Granger priežastiniai testai ir kointegracijos testai. Nustatyta, kad finansinės krizės metu Latvijos rinka tapo pasyviausia, nors iki prasidedant krizei buvo pati aktyviausia, pasyvesne tapo ir Estijos rinka. Taigi finansinis nuosmukis skaudžiausiai paveikė Latvijos ir Estijos finansų rinkas. Lietuvos ir Rusijos rinkos krizės metu tapo pačios aktyviausios ir lengviausiai išgyveno akcijų kainų kritimo perioda, tuo patvirtindamos, kad krizės metu daugelio investuotojų interesai ir lūkesčiai paprastai siejami su didesnemis rinkomis, kurios laikomos patikimesnėmis ir turinčiomis galimybę greičiau atsigauti. Reikšminiai žodžiai: finansų rinkos, ekonominis nuosmukis, Granger priežastingumo testai, empiriniai testai, bendrosios tendencijos. First published online: 10 Feb 2011